2020
DOI: 10.1007/s13592-020-00775-0
|View full text |Cite
|
Sign up to set email alerts
|

Varroa destructor rearing in laboratory conditions: importance of foundress survival in doubly infested cells and reproduction of laboratory-born females

Abstract: A considerable part of the knowledge about the honey bee parasite Varroa destructor emerged from rearing protocols in semi-natural or laboratory conditions, yet a durable protocol over several generations of mites is still lacking. The development of such multigenerational rearing relies on the emergence of a sufficient number of new fertile females in the first generation of V. destructor . The optimization of the parasite's reproductive success in laboratory conditions thus represents an important prerequisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
(96 reference statements)
2
4
1
Order By: Relevance
“…Statistical analysis showed no significant differences between P, F1, F2, and F3 generations for these variables (p > 0.05, GLMM results, Supplementary Table S2; Figure 2). As expected, the mean mite survival (95%) registered in our semi-field rearing experiment is higher than the values reported in in vitro rearing systems (80.5% in Jack et al (2020), 78.5 and 50% for the first and the second mite generations, respectively, in Piou et al (2020)). Regarding reproductive parameters analyzed on the remaining 1164 healthy female mites, we observed that 927 (79.64%) were fertile and 237 (20.36%) were non-fertile (Supplementary Table S1).…”
Section: Resultssupporting
confidence: 73%
“…Statistical analysis showed no significant differences between P, F1, F2, and F3 generations for these variables (p > 0.05, GLMM results, Supplementary Table S2; Figure 2). As expected, the mean mite survival (95%) registered in our semi-field rearing experiment is higher than the values reported in in vitro rearing systems (80.5% in Jack et al (2020), 78.5 and 50% for the first and the second mite generations, respectively, in Piou et al (2020)). Regarding reproductive parameters analyzed on the remaining 1164 healthy female mites, we observed that 927 (79.64%) were fertile and 237 (20.36%) were non-fertile (Supplementary Table S1).…”
Section: Resultssupporting
confidence: 73%
“…During this reproductive phase, mite reproduction was low compared to previous studies [59,60]. For the most part, bee mortality associated with the virus explained the reduced reproduction of the mite.…”
Section: Evolution Of Viral Loads In Mites During the Reproductive Ph...contrasting
confidence: 54%
“…Two brood frames from the uninfested indoor colony were taken to the laboratory and fifth instar larvae from unsealed cells were transferred into 0.33-ml gelatin capsules as described in [59,60]. The 40 V. destructor females retrieved at the end of the artificial infection experiment were introduced into the capsules containing healthy bee larvae.…”
Section: In Vitro Rearing Of Artificially Infected V Destructormentioning
confidence: 99%
See 2 more Smart Citations